The Relationship of Transformational Leadership Style with Bullying at Work with Regard to the Mediating Role of Organizational Health among Employees of Shiraz University of Medical Sciences - Ahmad Rastegar; Mohammad Hasan Seif; Zahra Firoozi Ardekani; Marzieh Tajvaran (Tehran University of Medical Sciences, 2019)
Background and Aim: Workplace bullying around the world is a work-injury factor, a mental health alarm and a global disaster. The aim of the present study was to investigate the relationship between transformational leadership and workplace bullying among employees at Shiraz University of Medical Sciences taking into account the mediating role of organizational health. Materials and Methods: The research method was descriptive - survey. Research instruments chosen for the purpose of this study included The multifactor leadership questionnaire as the standard instrument for measuring transformational leadership behavior Bass & Avolio with(0.79) reliability, Graham Lowe's standard questionnaire of organizational health questionnaire with(0.79) reliability and for organizational bullying a researcher-made questionnaire with(0/83) reliability was used. The statistical population of the study consisted of 265 university staff who were selected by simple sampling method. The research hypotheses were analyzed using SPSS and Lisrel 8.8 softwares and descriptive statistics and path analysis. Results: The results showed that the components of transformational leadership affected workplace bullying indirectly and negatively through the mediation of organizational health. In addition, among the components of transformational leadership, idealized influence had the highest indirect effect(-0/19) on workplace bullying.  Among the components of organizational health, vibrant workplace had the highest level of direct effect(-0/27) on workplace bullying. Conclusion: A good leadership style creates a healthy organization and reduces workplace bullying. Therefore, organizations need to develop organizational health and provide training, especially to managers of organizations.